Applications of classical singing techniques to pop singing case study: voice students and teachers in Kuala Lumpur / Fify Emielia Shazlin Ahmad Murshaidi - Ahmad Murshaidi, Fify Emielia Shazlin (2014)
This study seeks to know about the applications of classical singing techniques to pop singing. The case study of this research is a voice students and teachers in Kuala Lumpur This study also is to find out about selected classical singing techniques and pop singing techniques and how classical singing techniques apply to pop singing‘ It is also to identify which methods of classical singing are appropriate for pop singing In seeking greater understanding, this research is conducted in qualitative method of interviewing voice students and teachers around Kuala Lumpur who sings both classical and pop singing As a result, almost all of them realize and agree that some classical singing techniques really benefit pop singing. Some methods are useful and helping singers to improve on their pop singing after learning the classical singing techniques. All of them agree that learning classical singing techniques as a basic for greater foundation such as correct breathing techniques and the use of different voice register can help singers to improve their pop singing 100. As a recommendation, singers must know how to make use of what they had learn and must know which methods of singing are suitable for them to use in their pop singing because pop singing comes in different style of singing,